2005
DOI: 10.1080/1401543051006721
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sampling rate on accuracy and reliability of acoustic voice analysis

Abstract: It is universally recognized that sampling rate (F(S)) influences the reliability and validity of acoustic voice measurements; however, an exact relationship has not been determined. The purpose of this experiment was to investigate the influence of F(S) on acoustic voice quality measurements, while considering the influences of gender, intra-subject variability, microphone, environmental noise, data acquisition hardware, and analysis software as balancing factors. The impact of F(S), from 44.1 kHz to 10 kHz, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 12 publications
0
32
0
2
Order By: Relevance
“…Research has shown that F0 measurements are highly comparable across formats in the range of sampling rates used in the current studies, including recordings using lossy compression (mp3; e.g. Gonzalez et al 2003;Deliyski et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that F0 measurements are highly comparable across formats in the range of sampling rates used in the current studies, including recordings using lossy compression (mp3; e.g. Gonzalez et al 2003;Deliyski et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Here, the focus on comparing pre-and post-treatment characteristics, with all participants recorded using the same technology is the quantification of interest, not necessarily a claim that exact low levels of perturbation are reflective of exact vocal fold cycle-to-cycle variations per se. Additionally, higher sampling rates are preferable for absolute quantification of departures from pure periodicity [26] as high as 50 kHz or more, but for the algorithms to be utilized in this work it has been demonstrated that rates on the order of 20 kHz are acceptable [27] especially for the current design which focuses on relative levels of the measures.…”
Section: Speech Stimulimentioning
confidence: 99%
“…Not all acquisition environments are suitable for widespread acoustic investigation, especially when certain analysis systems are employed (Deliyski, Evans, & Shaw, 2005;Deliyski et al, 2005b;Smits et al, 2005) or the signal-to-noise ratio is unsuitable (Deliyski et al, 2005a;Ma & Yiu, 2005;Qi, Hillman, & Milstein, 1999). The use of less specialized equipment such as PCs can limit a study design in other ways.…”
Section: Perturbationmentioning
confidence: 99%
“…noise (Carson et al, 2003;Deliyski, Shaw, & Evans, 2005a;Deliyski et al, 2005b;Hillenbrand, 1987), data acquisition environments (Deliyski, Evans, & Shaw, 2005;Scherer, Vail, & Guo, 1995;Smits, Ceuppens, & De Bodt, 2005), sampling rates (Deliyski et al, 2005b;Parsa, Jamieson, & Pretty, 2001), the microphone selection Titze & Winholtz, 1993;Winholtz & Titze, 1997), the recording hardware used (Mundt et al, 2007), population characteristics (Lei, Yang, Shen, & Gong, 2000;Mueller, 1997;Scherer et al, 1995;Xue & Fucci, 2000), and the appropriateness of stimuli employed , almost every aspect of voice acoustics has been investigated in an effort to determine the minimum requirements for accurate and repeatable recording and analytical configurations. This body of work has yielded a broad set of criteria for acoustic analysis.…”
mentioning
confidence: 99%